Implementasi Metode Bernyanyi Mengubah Lagu dalam Menambah Mufrodat Bahasa Arab - Dini Astri Sari Sumarta (Al-Mada: Jurnal Agama, Sosial, dan Budaya, 2023)
Vocabulary is important think to mastering the language. In a language, the amount of vocabulary greatly influences a person's ability to use the language and support four language competences such as listening, reading, speaking and writing. Likewise in Arabic, mufrodat can support maharotul Istima’, maharotul Kalam, maharotul Qiroah and maharotul Kitabah. This Research aims to using singing method to mastering of Arabic vocabulary or mufrodat in class VII students SMPIT As Syifa Jalancagak Subang. This type of research is using PTK (Classroom Action Research) design, with two cycle’s model. Data collection techniques include observation of students, teacher and class activity, interview, and test. While the data analysis used is qualitative, the results of data analysis show that the learning process with singing methods can increase the students' Arabic vocabulary easily. The result of observation whose love to sing to memorize is 93,3%, who’s feel easier 86%,, who’s have interesting experience 100%, who’s choose singing method over conventional 73,33%. And the research was successful because there was an 80% increase in.